Dietary sulfur amino acid restriction in humans with overweight and obesity: a translational randomized controlled trial - Olsen, Thomas; Stolt, Emma; Øvrebø, Bente; Elshorbagy, Amany; Tore, Elena C.; Lee-Ødegård, Sindre; Troensegaard, Hannibal; Johannessen, Hanna; Doeland, Beate; Vo, Anna A. D.; Dahl, Anja F.; Svendsen, Karianne; et al. (Journal of translational medicine, 2024)
Background Dietary sulfur amino acid restriction (SAAR) improves metabolic health in animals. In this study, we investigated the effect of dietary SAAR on body weight, body composition, resting metabolic rate, gene expression profiles in white adipose tissue (WAT), and an extensive blood biomarker profile in humans with overweight or obesity. Methods N = 59 participants with overweight or obesity (73% women) were randomized stratified by sex to an 8-week plant-based dietary intervention low (~ 2 g /day, SAAR) or high (~ 5.6 g /day, control group) in sulfur amino acids. The diets were provided in full to the participants, and both investigators and participants were blinded to the intervention. Outcome analyses were performed using linear mixed model regression adjusted for baseline values of the outcome and sex. Results SAAR led to a ~ 20% greater weight loss compared to controls (β 95% CI − 1.14 (− 2.04, − 0.25) kg, p = 0.013). Despite greater weight loss, resting metabolic rate remained similar between groups. Furthermore, SAAR decreased serum leptin, and increased ketone bodies compared to controls. In WAT, 20 genes were upregulated whereas 24 genes were downregulated (FDR < 5%) in the SAAR group compared to controls. Generally applicable gene set enrichment analyses revealed that processes associated with ribosomes were upregulated, whereas processes related to structural components were downregulated. Conclusion Our study shows that SAAR leads to greater weight loss, decreased leptin and increased ketone bodies compared to controls. Further research on SAAR is needed to investigate the therapeutic potential for metabolic conditions in humans. Trial registration : ClinicalTrials.gov identifier: NCT04701346, registered Jan 8th 2021, https://www.clinicaltrials.gov/study/NCT04701346